Rhabdomyolysis in Children: A State-of-the-Art Review - Manson Chon In Kuok; Winnie Kwai Yu Chan (Children)
Rhabdomyolysis in pediatric patients is a rare but potentially life-threatening condition characterized by the breakdown of skeletal muscle fibers, leading to the release of intracellular components such as myoglobin, potassium, and creatine kinase into the bloodstream. This process can result in severe electrolyte imbalances and acute kidney injury (AKI), sometimes necessitating kidney replacement therapy. While rhabdomyolysis is well studied in adults, pediatric cases present unique diagnostic and therapeutic challenges due to distinct etiologies and clinical manifestations. This review explores the pathophysiology, etiologies, complications, treatment, and outcomes of rhabdomyolysis, with a particular focus on the pediatric population. Emerging evidence regarding the role of hemoadsorption in myoglobin removal is discussed and summarized. Additionally, we propose a systematic framework for the management and monitoring of these patients.